Effects of heat generation or absorption on mixed convection flow over a stretching porous wedge with convective boundary condition - Ashraf, M. (American Institute of Physics Inc., 2014)
The series solution of the boundary layer flow over a permeable stretching wedge with convective boundary condition has been investigated in the presence of heat generation or absorption effects. The governing coupled non-linear partial differential equations are transformed to dimensionless system of coupled non-linear ordinary differential equations using the similarity variables and then solved by Homotopy Analysis Method (HAM). An analysis of the results shows that the velocity and temperature fields are significantly influenced by the velocity ratio parameter, wedge angle parameter, suction/injection parameter, heat generation/absorption parameter and convective heat transfer parameter. Â© 2014 AIP Publishing LLC.